ECONOMIC EFFICIENCY AND THE ROLE OF THE STATE IN MARKET ECONOMY - ROŞCA, Petru (Annals of Spiru Haret University. Economic Series, 2017)
Economic efficiency emerges after comparing the effects of some action with the efforts needed to produce it and has general applicability in decision-making in any country. It can be said that economic efficiency is closely related to the use of resources in the economy and its essential feature is the stress/effects causal ratio. In the competitive system of the free market, the activity of the economic agents provides performance to the extent that it has a high efficiency. Any human activity is, at the same time, resources consuming and effects producing. In the economic theory, the concept of efficiency characterizes the activity developed in various fields: economic, social, educational, health, sports, etc. More concretely, it reflects the physical, intellectual and moral (in the deontological sense) effort made to achieve a goal or the pre-established objective, respectively the relationship between two waves: the resources spent and the resulting effects, expressed in physical (pieces, kg, and meter) or value (lei) units of measurement.